Iron-Catalyzed Direct Cross-Coupling of Ethers and Thioether with Alcohols for the Synthesis of Mixed Acetals - Han, Wei; Cheng, Lu; Zhao, Hongyuan (Synlett, 2020)
An iron-catalyzed direct O-alkylation of alcohols via α-C(sp3)–H activation of ethers and a thioether has been established that tolerates cyclic and acyclic ethers and alcohols containing aromatic N-heterocyclic moieties, providing an efficient and green method for the synthesis of mixed acetals with good to excellent yields. The robustness of this protocol is demonstrated by the late-stage oxidation of a structurally complex natural product.
Keywords: iron catalysis; oxidation; alcohols; ethers; mixed acetals; synthetic methods